Mathematical modeling in science and engineering : an axiomatic approach - Herrera, Ismael; Pinder, George Francis, 1942- (Hoboken, N.J. : Wiley, 2012)
'Mathematical and computational modeling (MCM) can be used in a diverse set of applications making it a very appealing and potent modeling tool. This book uses a novel and powerful procedural approach to teaching MCM, the Axiomatic Approach, which permits incorporating in a single model, systems that occur in many different branches of science and engineering.This book focuses on the mathematical models, in which processes to be modeled are expressed as a system of partial differential equations. It introduces a systematic method for constructing such models, which can be applied to any macroscopic physical system. This latter feature of the Axiomatic Approach is very valuable when treating new systems, since it permits formulating the models of previously unknown systems. Using it, many of the systems of most common occurrence in engineering practice are introduced and discussed. The effectiveness of this approach is reflected in the broadness and importance of the subjects treated; they cover a great diversity of topics that are basic in many branches of engineering including: Civil Engineering, Mechanical Engineering, Petroleum Engineering, and Water Resources.These topics include: Flow of fluids and transport of solutes which are free to move in the physical space and where fluids may be restricted to move in a porous medium. The transport of solutes is fundamental in Environmental Engineering Water Resources and Petroleum Engineering since it is the means of predicting contaminant behavior. The porous medium based equations are also used to model Enhanced Oil Recovery which is very important for sustaining the oil supply of the world. Model of static and dynamic elasticity are used in several branches of engineering including Foundation and Seismic Engineering'--Provided by publisher.
'This book uses a novel and powerful procedural approach to teaching MCM, the Axiomatic Approach, which permits incorporating in a single model, systems that occur in many different branches of science and engineering'--Provided by publisher.
Includes bibliographical references and index.
Keywords: System analysis -- Mathematical models; Science -- Mathematical models; Engineering -- Mathematical models